2018
DOI: 10.3390/ijms19123823
|View full text |Cite
|
Sign up to set email alerts
|

α-Melanocyte-Stimulating Hormone Attenuates Neovascularization by Inducing Nitric Oxide Deficiency via MC-Rs/PKA/NF-κB Signaling

Abstract: α-melanocyte-stimulating hormone (α-MSH) has been characterized as a novel angiogenesis inhibitor. The homeostasis of nitric oxide (NO) plays an important role in neovascularization. However, it remains unclear whether α-MSH mitigates angiogenesis through modulation of NO and its signaling pathway. The present study elucidated the function and mechanism of NO signaling in α-MSH-induced angiogenesis inhibition using cultured human umbilical vein endothelial cells (HUVECs), rat aorta rings, and transgenic zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Consistently, our previous studies have demonstrated that the gene delivery of proopiomelanocortin (POMC), the precursor of alpha-melanocyte stimulating hormone (α-MSH), effectively suppresses the progression and metastasis of melanoma though the inhibition of COX-2/PGE2 signaling [24]. Among the POMC-derived peptides, α-MSH has been delineated to participate in the anti-neoplastic mechanism of POMC gene therapy via inflammation inhibition [24], neovascularization blockade [25,26], and sensitizing cancer cells to hypoxia-induced apoptosis [27].…”
Section: Introductionmentioning
confidence: 68%
“…Consistently, our previous studies have demonstrated that the gene delivery of proopiomelanocortin (POMC), the precursor of alpha-melanocyte stimulating hormone (α-MSH), effectively suppresses the progression and metastasis of melanoma though the inhibition of COX-2/PGE2 signaling [24]. Among the POMC-derived peptides, α-MSH has been delineated to participate in the anti-neoplastic mechanism of POMC gene therapy via inflammation inhibition [24], neovascularization blockade [25,26], and sensitizing cancer cells to hypoxia-induced apoptosis [27].…”
Section: Introductionmentioning
confidence: 68%
“…The angiogenesis of human vessel endothelial cells incubated in ONFH serum was performed using BD BioCoat™ angiogenesis kits (BD Biosciences, San Jose, CA, USA), as previously described [49]. In brief, human umbilical vessel endothelial cells (5 × 10 4 cells/well, 48 well-plates; American Type Culture Collection) were incubated in ONFH serum, with or without 1 μg/mL S100A9 antibody, IgG (Abcam, Cambridge, UK), 250 ng/mL S100A9 (R&D Systems, Minneapolis, MN, USA) and incubated in a humidified incubator at 37 °C for 6 h. In a subset of experiments, the cells were incubated in 250 ng/mL VEGF as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…2012122901). The protocols for vessel outgrowth of aortic rings were performed, as previously described [49]. In brief, 6 male Sprague-Dawley rats (3 months old) were euthanatized.…”
Section: Methodsmentioning
confidence: 99%
“…Many successful studies addressing the molecular mechanisms of blood vessel development, such as angioblast specification and migration, vascular endothelium proliferation and migration, and vessel formation and patterning, have been conducted using zebrafish as a model organism [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Furthermore, the effects of chemicals and drugs on the development of vasculature have been successfully addressed in the zebrafish model [ 12 , 13 , 14 , 15 , 16 ]. For example, we reported that the marine compound WA-25 inhibits angiogenesis [ 13 ], GB9 impairs vascular development [ 14 ], and heteronemin (SP1) suppresses lymphangiogenesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%